S. Dube (2017), Formaciones de lo contemporáneo. México: El Colegio de México. 248 pp. - Rufer, Mario (Estudios de Asia y África, 2019)
S. Dube (2017), Formaciones de lo contemporáneo. México: El Colegio de México. 248 pp.